Shorted Happiness at Work Scale: Psychometric Proprieties of the Portuguese Version in a Sample of Nurses - Feitor, Sofia (2023)
In the last decades, happiness at work has been studied due to social changes; increased workload; stress; and, more recently, the COVID-19 pandemic. Happiness at work is considered an umbrella concept as it covers individual and organizational aspects of working life. The aim of this study is to analyze the psychometric properties of the Shorted Happiness at Work Scale (SHAW) in a sample of Portuguese nurses. A cross-sectional study with 113 Portuguese nurses, from one of the islands of the Azores, was selected through a convenience sample. A sociodemographic/professional questionnaire and the SHAW scale were applied. Through the CFA, the SHAW trifactorial model was tested according to its theoretical reference, having obtained a general tolerable adjustment index. After respecification of the model through the correlation of the errors of two items, a better adjustment was obtained, but the RMSEA value remains problematic. Additionally, the values of the coefficient of internal consistency were indicative of good fidelity. The analysis of the psychometric characteristics of the SHAW scale, in the sample of Portuguese nurses, suggests a theoretical adaptation to the model of happiness at work.